Urban governance in Asia : sub-regional and city perspectives - Islam, Nazrul, 1941-; University of Dhaka. Centre for Urban Studies (Dhaka, Bangladesh : Centre for Urban Studies ; Pathak Shamabesh, 2000)
Contributed articles.
Includes bibliographical references.
Keywords: Regionalism -- South Asia; South Asia -- Politics and government